Trauma exposure and psychometric properties of the life events checklist among adults in South Africa. Issue 1 (31st December 2023) - Stevenson, Anne; Beltran, Marine; Misra, Supriya; Ametaj, Amantia A.; Bronkhorst, Aletta; Gelaye, Bizu; Koenen, Karestan C.; Pretorius, Adele; Stein, Dan J.; Zingela, Zukiswa
ABSTRACT: Background: Trauma exposure is widespread and linked to chronic physical and mental health conditions including posttraumatic stress disorder. However, there are major gaps in our knowledge of trauma exposure in Africa and on the validity of instruments to assess potentially life-threatening trauma exposure. Objective: The Life Events Checklist for the DSM-5 (LEC-5) is a free, widely used questionnaire to assess traumatic events that can be associated with psychopathology. As part of a case–control study on risk factors for psychosis spectrum disorders, we used the LEC-5 to examine the frequency of traumatic events and to assess the questionnaire's factor structure in South Africa ( N = 6, 765). Method: The prevalence of traumatic events was measured by individual items on the LEC-5 across the study sample, by case–control status, and by sex. Cumulative trauma burden was calculated by grouping items into 0, 1, 2, 3, and ≥4 traumatic event types. Psychometric properties of the LEC-5 were assessed through exploratory and confirmatory factor analyses. Results: More than 92% of the study sample reported experiencing ≥1 traumatic event; 38.7% reported experiencing ≥4 traumatic event types. The most endorsed item was physical assault (65.0%), followed by assault with a weapon (50.2%). Almost 94% of cases reported ≥1 traumatic event compared to 90.5% of controls ( p < .001) and 94% of male participants reported ≥1 traumatic event compared to 89.5% of female participants ( p < .001). Exploratory factor analysis revealed a 6-factor model. Confirmatory factor analyses of three models found that a 7-factor model based on the South African Stress and Health survey was the best fit (standardized root mean square residual of 0.024, root mean square error of approximation of 0.029, comparative fit index of 0.910). Conclusion: Participants reported very high exposure to traumatic events. The LEC-5 has good psychometric priorities and is adequate for capturing trauma exposure in South Africa. HIGHLIGHTS : Trauma exposure was extremely prevalent in this South African sample, with less than 8% of participants reporting zero exposure to traumatic events. This was the first time the factor structure of the LEC-5 was assessed in South Africa. A confirmatory factor analysis using a 7-factor model based on a previous study of trauma exposure, the South African Stress and Health study (SASH), was the best fit for the LEC-5.